The influence of group membership on the neural correlates involved in empathy - Eres, Robert; Molenberghs, Pascal (Frontiers in Human Neuroscience, 2013)
Empathy involves affective, cognitive and emotion regulative components. The affective component relies on the sharing of emotional states with others and is discussed here in relation to the human Mirror System. On the other hand, the cognitive component is related to understanding the mental states of others and draws upon literature surrounding Theory of Mind. The final component, emotion regulation depends on executive function and is responsible for managing the degree to which explicit empathic responses are made. This mini-review provides information on how each of the three components is individually affected by group membership and how this leads to in-group bias.